Fermentation optimization of ER2738 – E. coli host cells for mass production of bacteriophages of agricultural importance - Radhi, Mohd Zafrul Arif; Adam, Mohd Bakri; Mohd Saud, Halimi; Hamid, Mohd Norowi; Peng, Tony Shih Hao; Tan, Geok Hun (Penerbit MARDI, 2018)
Bacteriophages are viruses that infect and replicate within bacteria and archae. Recent studies have isolated bacteriophages of agricultural importance – which can be used as an alternative to combat diseases caused by bacterial pathogen in plants. In order to be effective, high titre of bacteriophages are needed in application for particular bacterial diseases in plants. In order to amplify the phages of interest, the bacterial host need to be produced massively. In this study, the production of E. coli host cells (ER2738) had been done by fermentation using a bioreactor. Compared with the usage of standard shake flask, the fermentation by bioreactor is more efficient in terms of quality and quantity of the bacterial cells produced since the process was done in more controlled and optimized settings, which gives high yield with minimized risk of contamination. Therefore, this study intends to choose better growth medium between LB Broth (F1) and Terrific Broth (F2) to be used in the amplification of host cells, ER2738 using bioreactor. The mode of fermentation used in this study was the batch fermentation. F2 was found to record higher bioass count at 10 hours which was 0.0116g/mL compared with F1 which recorded 0.0020g/mL. Population count of E. coli peaked earlier in F2 at 6 hours while in F1, the population count peaked at 14 hours. Generally, along the fermentation process, the optical density for F2 was higher than F1.